The Effect of Using Semantic Mapping Strategy on Reading Comprehension of Grade Eight Students at SMP Negeri 12 Pematangsiantar - Damanik, Danny Boy; Munthe, Melda Veby Ristella; Purba, Rudiarman (Universitas Pahlawan Tuanku Tambusai, 2025)
This research was carried out to find out the effect of using Semantic Mapping Strategy on reading comprehension of grade eight students at SMP Negeri 12 Pematangsiantar. This research employed a quasi-experimental design with a quantitative approach. The population of this research was eight grade students of SMP Negeri 12 Pematangsiantar in academic year 2024/2025. The researcher took two classes as the sample. The sample were VIII-1 as the experimental group consisted of 31 students and VIII-2 as the control group consisted of 31 students. The experimental group was taught by using semantic mapping strategy meanwhile control group was taught by conventional strategy. The data were obtained by using pre-test and post-test given to both groups. The experimental group mean score was 27,2 on the pretest and on the post test was 64,84. Meanwhile, the mean score of the control group was 32,42 on the pretest and 55,32 on the posttest. To acquire the data, the researcher used multiple choice test as an instrument. The data analyzed using IBM SPSS version 30.0. The result of t-test was sig. two tailed 0.04 which lower than sig. 0.05 it indicates that alternate hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. Therefore there was significant effect by using Semantic Mapping Strategy on students reading comprehension of grade eight students at SMP Negeri 12 Pematangsiantar.